(untitled) (Journal of Pharmaceutical Negative Results, 2023)
The quality of yarn is largely determined by the properties of the fibers from which it is produced. There is a certain correlation between the properties of the fibers and the yarn. Toothed feeding cylinders with elastic casings act on the fiber tape according to the laws of mechanics. Thin shells are widely used in the design of elements in many branches of modern technology, particularly in mechanical engineering. In this feeding cylinder thin shells are installed, which helps to obtain high-quality yarn on rotor spinning machines. The calculated results of the feed cylinder with elastic casings in the feed area of rotor spinning machines are given. Each parameter is conditionally discussed according to the laws of dynamics and resistance of materials.